Feminism and marginalized black women in the Hood Feminism novel by Mikki Kendall (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
The purposes of this study are to find out gender inequality and racism cases experienced by the author in Hood Feminism novel. There are some cases related to gender inequality, such as, patriarchal ideology, violation and discrimination against a community, while racism cases cover poverty, gun violence, hunger, injustice, and inadequate education to marginalized communities. The cases that have been studied are then linked with other cases of the same nature from one chapter to another based on Black Feminism approach, so that later conclusions can be drawn from the research. With the obstacles and burdens in carrying out these efforts, this novel becomes interesting to study. The main character in the novel herself also plays a role in the effort to get her rights as black woman. The experience of the main character in the novel is also a supporting factor that creates real facts or evidence, which is also a representation of her own experience that occur in the environment of the community.